Sentinel Lymph Node Biopsy - Clinical Experience - Paz, Wagner Antonio (2001)
Axillary dissection may be currently the most controversial topic in the treatment of small invasive breast cancer. Beside the need of accurate axillary staging, there is the morbidity associated with conventional axillary dissection. The sentinel lymph node biopsy is emerging as a selective axillary sampling method, minimally invasive and highly sensitive in identifying metastases. We report our initial clinical experience with the technique on 47 patients with breast cancer in a period of two years. Lymphoscintigraphy, the method used for identification of the sentinel lymph nodes, was positive in 95,7%. Sentinel nodes were found in 91% of patients with successful lymphatic mapping. The mean number of sentinel lymph nodes per patient was 1,6. The detailed histopathologic examination of the sentinel lymph nodes was obtained by serial sectioning. Immunohistochemical staining was used as an additional method on 12 patients. We report only one case of metastasis in a sentinel node and sub sequentially complementary axillary dissection. In this case the sentinel node has been confirmed as the only metastatic axillary node. The sentinel lymph node biopsy has become the standard axillary approach of small invasive breast cancer patients without clinical axillary involvement at our Institution.